Studi Penciptaan Batu Bata Ekspos Bermotif Lokal - Marwanto, Aries Budi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2011)
The focus of this study is divided into two major parts, the first is the search for material composition mixture of clay as the main material of brick making and the second is the development of product design to conventional brick-patterned brick exposed locally. The long term goal of this research in addition to improving product variants that have a competitive national and global markets. Research design in the creation of this study is exploratory research, a process of â€œtrial and seeâ€ or controlled trial. Techniques of data collection was conducted by researchers observations (the process of making brick and clay soil sampling is used), interviews brick craftman in the district. Mojolaban (associated with a brick making technology) and literature searches (related on the clay-forming elements and some chemical elements as reinforcing material clay). Data is processed and tested in the laboratory with a ceramic combustion process, then selected a mixture of clay formula which is most suitable for making bricks. After successfully making quality bricks (strong and precision), then make the exposed brick with ornamnetal motifs develop tradition of batik motifs develop in Surakarta. Keywords : brick,ornamnet, batikÂ